Optimization of heat load in three-stage distillation of vegetable oil micelles - Ikromova, Yulduzxon; Nuriddinov, Shohjahon; Hamdamov, Anvar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article presents methods of effective use of secondary water vapor in three-stage distillation of vegetable oil micelles, optimization of material and heat consumption of solvent vapor, water vapor and water in distillation processes. Economic efficiency was calculated as a result of efficient use of energy of secondary solvent vapors, saving of cold water consumption and introduction of energy-efficient technological line.